Factors associated with hard tick (Acari: Ixodidae) parasitism in medium-sized mammals in the Atlantic Rainforest region of Argentina - Lamattina, Daniela; Costa, Sebastián Andrés; Arrabal, Juan Pablo; Venzal, José Manuel; Guglielmone, Alberto; Nava, Santiago (2018)
Associations with environmental and host parameters were assessed to describe tick parasitism patterns in two medium-sized mammals of the Atlantic rainforest region of Argentina. Ticks found on 93 specimens of Nasua nasua and 26 specimens of Didelphis aurita captured at six sites in the Iguazú National Park were collected. Generalized linear models were constructed to explain the presence and abundance of ticks and the most appropriate ones were selected after stepwise simplification. The season, site and host body mass variables were important to explain the abundance of Amblyomma coelebs nymphs, while site was important to describe larval abundance of this species. Season was the most important variable for larvae and nymphs of Haemaphysalis juxtakochi, while Amblyomma brasiliense nymphs were associated with host age. Amblyomma ovale larvae were related to host age, and adult ticks with host sex. The results indicate that these medium-sized mammals are important to support the immature tick stages and that both host and environmental factors may be associated with parasite loads.